Fosfato natural na adubação do capim piatã em latossolo vermelho do cerrado - Rezende, Cristina Gonçalves Barbosa (2013)
The Oxisols have high phosphorus fixation capacity due to the acidity and the source material. That makes phosphate fertilization be fundamental for this would not be a limiting factor in the establishment and production of pastures. The natural phosphate is alternative to pasture fertilization, presenting lower cost per unit of P2O5 and high residual effect of the element in the soil. Thus, aimed to by the present study was to evaluate the effect of rock phosphate as a source of phosphorus in the development and production of Brachiaria brizantha cv. Piatã in Cerrado Oxisol. The experiment was conducted in the greenhouse of the University campus Rondonópolis Federal University of Mato Grosso. The treatments were constituted by application of 0, 100, 200, 300, 400 and 500 mg dm-3 of phosphorus (P2O5) disposed in a completely randomized and design with eight replications. Were evaluated the heigh to plants, chlorophyll content, leaf number, tiller number, leaf dry weight, shoot dry mass, dry mass of stem, leaf / stem ratio, root dry weight and soil pH. The results were submitted to analysis of variance by F test at 5% probability, and when was significant performed regression study for phosphorus dose 5% probability, by means of the statistical SISVAR. The values found for height were: 80,04; 90,69 and 66,73 cm obtained with doses of 378,13; 300 and 338,33 mg dm-³ respectively for the three cuts. The number of tillers in the first two cuts were 33 and 43 tillers pot-1 for phosphorus doses of 382,35 and 366,67 mg dm-3. The natural phosphate positively influences the development and production of grass Piatã cultivated in Cerrado Oxisol.